2019
DOI: 10.1111/jce.14154
|View full text |Cite
|
Sign up to set email alerts
|

Association between epicardial adipose tissue and embolic stroke after catheter ablation of atrial fibrillation

Abstract: Introduction Risk factors of embolic stroke (ES) after atrial fibrillation (AF) ablation have not been fully elucidated especially among the Asian subjects, particularly regarding epicardial adipose tissue (EAT) in cardiac imaging. We aimed to assess the incidence of ES during a long‐term follow‐up period after AF ablation and to identify the risk factors associated with postablation ES, specifically focusing on EAT. Methods and Results We enrolled patients who experienced postablation ES and control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…9 Additionally, the long-term risk of embolic stroke in patients with AF submitted to catheter ablation is higher among patients with larger pEAT volume, and this association appears to be independent of AF recurrence. 10 In another study of patients with persistent AF, the majority of whom were not anticoagulated, increased pEATT was also associated with an increased risk of cardiovascular events. 11 A systematic review of 8 small studies has recently suggested an increased risk of stroke with increased epicardial adipose tissue, but there was marked heterogeneity in the study populations and methodologies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 Additionally, the long-term risk of embolic stroke in patients with AF submitted to catheter ablation is higher among patients with larger pEAT volume, and this association appears to be independent of AF recurrence. 10 In another study of patients with persistent AF, the majority of whom were not anticoagulated, increased pEATT was also associated with an increased risk of cardiovascular events. 11 A systematic review of 8 small studies has recently suggested an increased risk of stroke with increased epicardial adipose tissue, but there was marked heterogeneity in the study populations and methodologies.…”
Section: Discussionmentioning
confidence: 97%
“…In patients with AF undergoing pulmonary vein isolation, epicardial adipose tissue volume measured in CT is associated with AF recurrence 9 . Additionally, the long‐term risk of embolic stroke in patients with AF submitted to catheter ablation is higher among patients with larger pEAT volume, and this association appears to be independent of AF recurrence 10 . In another study of patients with persistent AF, the majority of whom were not anticoagulated, increased pEATT was also associated with an increased risk of cardiovascular events 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased EAT thickness has been associated with recurrence of AF after ablation ( 63 ). Larger peri atrial EAT volume is also related to the occurrence of embolic stroke after catheter ablation of AF ( 64 ). Some studies have failed to find an association between EAT and AF recurrence after catheter ablation, and it may depend on the stage of AF (paroxysmal vs. persistent) ( 65 ).…”
Section: Implications For Treatment and Future Directionsmentioning
confidence: 99%
“…The authors went on to perform receiver operator curve analysis and showed that a cut-off value of 20.15 mL resulted in an area under the curve of 0.658. Taken together, Ahn et al9 conclude from their data that peri-atrial EAT is independently associated with postablation embolic stroke and that assessment of peri-atrial EAT may have possible clinical utility in the identification of patients at higher risk. While Ahn et al 9 have provided further data supporting a possible link between EAT and the occurrence of postablation embolic stroke, larger studies are required to confirm this association and the potentially causative mechanisms established.…”
mentioning
confidence: 92%
“…Ahn et al9 in the current issue of the Journal of Cardiovascular Electrophysiology. In this paper, the authors investigated the factors associated with embolic stroke after catheter ablation of AF over a long-term follow-up period.…”
mentioning
confidence: 99%